Pengaruh Sosial Media Marketing Dan E-Wom Terhadap Minat Beli Produk The Originote Di Bandar Lampung - Effendi, Theresia; Defrizal, Defrizal (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The objective of this study is to investigate how social media marketing and e-WOM impact the purchase intention of The Originote products in Bandar Lampung. This research adopts a quantitative approach, utilizing a non-probability sampling method with a sample size of 100 respondents. Data collection is carried out through the distribution of questionnaires. The study incorporates validity testing, multiple linear regression, reliability testing, coefficient of determination, and subsequently performs T-test and F-test. The results reveal that the Social Media Marketing variable (X1) affects the purchase intention variable (Y) of The Originote products in Bandar Lampung, whereas the e-WOM variable (X2) does not significantly influence the purchase intention (Y) of The Originote products in Bandar Lampung. The combined impact of social media marketing (X1) and e-WOM (X2) simultaneously has a significant positive effect on the purchase intention (Y) of The Originote products in Bandar Lampung.